Treatment with low-dose tacrolimus inhibits bleeding complications in a patient with hereditary hemorrhagic telangiectasia and pulmonary arterial hypertension. (November 2018) - Sommer, N; Droege, F; Gamen, KE; Geisthoff, U; Gall, H; Tello, K; Richter, MJ; Deubner, LM; Schmiedel, R; Hecker, M; Spiekerkoetter, E; Wirsching, K; et al.
Pulmonary arterial hypertension (PAH) can be found in patients suffering from a loss-of-function mutation of the gene encoding for the activin receptor-like kinase 1 (ALK-1), a bone morphogenetic protein (BMP) type 1 receptor. Interestingly, ALK-1 mutations also lead to hereditary hemorrhagic telangiectasia (HHT), an autosomal dominant disease characterized by arteriovenous malformations (AVMs) leading to potentially life-threatening bleeding complications such as epistaxis. Current therapeutic options for both diseases are limited and often only temporary or accompanied by severe side effects. Here, we report of a patient with a mutation of the ALK-1 gene suffering from both HHT and PAH. Recently, it was shown that tacrolimus increased ALK-1 signaling and had beneficial effects in selected end-stage PAH patients. We thus hypothesized that treatment with tacrolimus may prevent disease progression in this patient. Surprisingly, treatment with low-dose tacrolimus dramatically improved his HHT-associated epistaxis but did not attenuate progression of PAH.